2023
DOI: 10.33480/jitk.v8i2.4004
|View full text |Cite
|
Sign up to set email alerts
|

Sentiment Analysis of Online Gojek Transportation Services on Twitter Using the Naïve Bayes Method

Abstract: Abstract— Social media is the most accessed internet content by internet users in Indonesia. This is not surprising, given the many benefits that social media provides, one of which is the benefit of self-expression. Self-expression can include many things, including emotional openness, which is the openness of a person in conveying the emotions he is feeling. Along with the development of social media, emotional disclosure is ubiquitous in social media, one of which is social media Twitter. With the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…This research proves that Chatbots such as Chat GPT-3.5 Open AI and Google Bard can be considered as alternative text pre-processing methods in Sentiment Analysis, offering an option alongside Python-based text pre-processing as presented in studies [5], [24]- [26], or solely relying on Rapidminer as shown in studies [3], [4], [6], [21], [22]. This research stands out as unique compared to previous studies because it combines widely used Text Pre-Processing tools like Rapidminer with Artificial Intelligence products, namely Chat GPT-3.5 Open AI and Google Bard.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This research proves that Chatbots such as Chat GPT-3.5 Open AI and Google Bard can be considered as alternative text pre-processing methods in Sentiment Analysis, offering an option alongside Python-based text pre-processing as presented in studies [5], [24]- [26], or solely relying on Rapidminer as shown in studies [3], [4], [6], [21], [22]. This research stands out as unique compared to previous studies because it combines widely used Text Pre-Processing tools like Rapidminer with Artificial Intelligence products, namely Chat GPT-3.5 Open AI and Google Bard.…”
Section: Discussionmentioning
confidence: 54%
“…Previous research has predominantly utilized Rapidminer applications, as seen in studies [3], [4], [6], [21], [22], while others have used Python, as seen in studies [5], [23]- [26]. The average accuracy value resulting from these three studies using Python is 73.33%.…”
Section: Introductionmentioning
confidence: 99%
“…Naïve Bayes is one of the techniques for developing a classification that combines probability and statistical methods with "naive" to manage conditions between attributes independently [16]. Naïve Bayes shown high accuracy and easy to train compared to the other machine learning algorithms with low error rate for large dataset [17]. Naïve Bayes algorithm is used to predict the likelihood of a specific word belonging to a specific class.…”
Section: Naïve Bayesmentioning
confidence: 99%
“…Therefore, several methods can be employed to shorten the time of the sentiment analysis process on the tweet data. One method that can be used to analyze the sentiment of a matter is the Naïve Bayes method or algorithm [9], [10]. The Naïve Bayes algorithm is based on the Bayes principle, which explains that all events have contributions of equal importance or independence concerning selecting a particular class.…”
Section: Introductionmentioning
confidence: 99%